1999
DOI: 10.1007/s100249900089
|View full text |Cite
|
Sign up to set email alerts
|

Huge Fetal Sacrococcygeal Teratoma with a Completely Formed Eye and Intratumoral DNA Ploidy Heterogeneity

Abstract: Preterm infants and newborns with sacrococcygeal teratomas are at high risk for prenatal and perinatal complications. The prognosis depends on size and histology of the tumor, degree of prematurity, associated malformations, route of delivery, and prompt and complete surgical removal. Virtually any tissue can be present in a sacrococcygeal teratoma, but to date, ocular lens has been documented only as lentinoids (lens-like cells), whereas flow-cytometric data have been variably interpreted. We describe a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The ovoid homogeneous lamellar structures recognized in the central nervous tissue were considered to be a crystalline lens. There was a human case of a sacrococcygeal teratoma with a completely formed eye in 29 weeks-infants, but there have been no papers reporting crystalline lens in canine teratomas [23]. However, it is sufficiently possible to being differentiated for optic that the optic structures can be differentiated from the tumor cells when considered their multipotential nature.…”
mentioning
confidence: 99%
“…The ovoid homogeneous lamellar structures recognized in the central nervous tissue were considered to be a crystalline lens. There was a human case of a sacrococcygeal teratoma with a completely formed eye in 29 weeks-infants, but there have been no papers reporting crystalline lens in canine teratomas [23]. However, it is sufficiently possible to being differentiated for optic that the optic structures can be differentiated from the tumor cells when considered their multipotential nature.…”
mentioning
confidence: 99%
“…Teratomas with a retina-like structure have been reported and some of the cases showed a complete or partial eye structure (9). A retrospective search in our medical center revealed that 2 out of 7 cases of sacrococcygeal teratoma of newborns had retina-like structures; one is the present case and the other showed an incompletely stratified retinal structure associated with retinal markers.…”
Section: Discussionmentioning
confidence: 58%
“…For example, one article states that aggregates ''resemble normal embryonic development much closer than previously thought,'' exhibiting ''an unexpected degree of self-organization'' [97]. Yet stem cell aggregates do not resemble organisms so much as they resemble tumors, which can also show a surprising degree of self-organization, producing well-formed teeth [98] and, even in one case, a remarkably normal eye [99].…”
Section: Behaving Like Part Of An Embryo or Merely Looking Like An Emmentioning
confidence: 95%